CENTRALIZED COGNITIVE ASSESSMENT IN A MULTICENTER TRIAL OF TREATMENT MODES FOR ASYMPTOMATIC CAROTID ARTERY DISEASE. (11th November 2018) - Wadley, V; Howard, V; Knopman, D; Lal, B; Meschia, J; Howard, G; Brott, T; Lazar, R
Abstract: The Carotid Revascularization and Medical Management for Asymptomatic Carotid Stenosis Trial (CREST-2) involves 123 clinics assessing intensive medical management (IMM) alone compared to either carotid endarterectomy plus IMM or carotid stenting plus IMM. Cognitive function is assessed prior to treatment and yearly thereafter. The neurocognitive battery, administered via telephone by interviewers at a university Survey Research Unit, includes measures administered in identical fashion in the REasons for Geographic and Racial Differences in Stroke (REGARDS) study. Learning and memory (CERAD Word List Learning-WLL and Word List Delay Recall–WLD) and executive function (animal—AF and letter fluency—LF) are assessed. We compared the baseline assessments of the first 207 CREST-2 participants with normative data drawn from >5000 REGARDS participants without stroke. We compared demographics-adjusted z-scores, as well as observed frequencies and confidence intervals for the 95th, 75th, 50th, 25th and 5th percentiles in each study. CREST-2 participants had a mean age of 69; 59% were men. Their mean scores for WLL, WLD, and LF were significantly lower than those in REGARDS (p values <=.05, <0.0001, and <.01, respectively). Similarly, the distribution of observed Z-scores skewed significantly lower for these tests at nearly all percentile ranks. AF scores were no different from those in REGARDS. Baseline cognitive scores among the first 207 participants in CREST-2 were significantly lower than the REGARDS group. These data support the sensitivity of a telephone-based test battery to detect differences in cognition and justify its use in a multicenter clinical trial to detect changes in cognitive function.